Efektifitas Project Based Learning-STEM dan Pemecahan Masalah Matematis Siswa pada Materi Trigonometri - Priatna, Nanang; Avip, Bambang; Mulyati Mustika Sari, Rika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2022)
The purpose of this study was to analyze the effectiveness of Project Based Learning-STEM (PjBL-STEM) associated with the variable Mathematical Problem Solving Ability (KPM) on trigonometric material. The research method uses a quasi-experimental design with Nonequivalent Control Group Design. The problem-solving abilities studied include: understanding the problem, planning for completion, completing according to plan, re-examining the calculation results. The results and conclusions of this study are (a) the effectiveness of the learning process of teachers and students can be categorized as good based on the average results on the observation sheet that has been assessed by the observer; (b) based on independent t-test there are differences in the improvement of students' mathematical problem solving abilities who receive STEM-based Project Based Learning (PjBL-STEM) learning with conventional learning, where STEM-based Project Based Learning (PjBL-STEM) learning has an average score N-gain 0.53 higher than conventional learning with an average N-Gain 0.31. Keywords: Project Based Learning; STEM; Problem Solving